A systematic review and meta-analysis of bond strength studies associated with self-etching primer and HF acid etching of dental glass-ceramics. (October 2022) - Awad, Mohamed M.; Alhalabi, Feras; Alotaibi, Nawaf; Alzamil, Faisal; Binalrimal, Sultan; Alrahlah, Ali; Ahmed, Mohammed H.
Abstract: Objective: This review aims to provide a qualitative and quantitative evaluation of the effect of self-etching ceramic primer (SECP) on the resin–ceramic bond strength, as reported in published in-vitro studies. Materials and methods: Three databases (MEDLINE "PubMed", Scopus and Web-of-Science) were electronically searched to identify studies that evaluated the effect of SECP on the bond strength to glass-ceramics versus the conventional treatment (hydrofluoric acid (HF) etching + silane-primer (S) application). Meta-analysis was conducted with RevMan version 5.4 software, Cochrane Collaboration; Copenhagen, Denmark using a random effect model, considering the bond strength evaluation after artificial aging. Results: Thirty-six studies satisfied the inclusion criteria for qualitative analysis, while only 18 studies were included in the quantitative analysis (meta-analysis). Twenty-three studies (63.9%) of the included studies showed a medium-risk of bias. The meta-analysis results showed no statistically significant difference ( p  ≥ 0.05) between resin-ceramic bond strength achieved following SECP or HF + S treatment with micro-shear bond strength (μSBS), tensile bond strength (TBS), and micro-tensile bond strength (μTBS) evaluation. However, shear bond strength (SBS) evaluation showed significantly less bond strength of SECP compared with HF + S (p < 0.00001). Conclusion: SECP application can effectively promote adequate resin–ceramic bonding despite its mild etching capacity. However, more in-vitro studies that involve long-term clinically relevant artificial aging, and further clinical studies are required before SECP can be considered as an alternative to the conventional surface treatment (HF + S) of glass-ceramic materials.